2003
DOI: 10.1002/aoc.530
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and cytotoxicity of silylalkylthio‐substituted N‐heterocycles and their hydroselenites

Abstract: New hydroselenites of the different silylalkylthio-substituted N-heterocycles have been prepared by the reaction of selenium dioxide with N-heterocycles in an aqueous medium. Their structure was confirmed by 1 H, 13 C, and 77 Se NMR data. Most of these silylalkylthio-substituted N-heterocycles and their hydroselenites have an expressed cytotoxic activity on the MG-22A (mouse hepatoma), HT-1080 (human fibrosarcoma), B16 (mouse melanoma), and Neuro 2A (mouse neuroblastoma) cell lines. Some of the hydroselenites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Another aim of this study was to test the importance of the presence of hydroselenite salt in the formulation. Previously, some studies of Arsenyan et al [47][48][49] have reported the cytotoxic activity against hepatoma, fibrosarcoma, melanoma, neuroblastoma of some heterocycles formulated as hydroselenites. Taking into account the above aforementioned we concluded that the effect of hydroselenite salts formulation depends of the central scaffold.…”
Section: Introductionmentioning
confidence: 99%
“…Another aim of this study was to test the importance of the presence of hydroselenite salt in the formulation. Previously, some studies of Arsenyan et al [47][48][49] have reported the cytotoxic activity against hepatoma, fibrosarcoma, melanoma, neuroblastoma of some heterocycles formulated as hydroselenites. Taking into account the above aforementioned we concluded that the effect of hydroselenite salts formulation depends of the central scaffold.…”
Section: Introductionmentioning
confidence: 99%
“…The basic drawback of furocoumarins is their high phototoxicity. On the other hand, the synthesis and investigation of a series of organic and inorganic selenium compounds in many cases revealed a wide spectrum of biological activity, in particular selenium-containing derivatives showed the possibility of their use in the treatment of malignant tumors [4][5][6].With the objective of producing new potentially biologically active heterocyclic systems we have developed a preparative method for the synthesis of the methyl ester of 3-bromo-2-(2-hydroxy-2-propyl)-7-oxo-7H-selenolo[2,3-f]chromene-8-carboxylic acid -a new example of a class of selenophene-containing polycyclic heterocycles. The methyl ester of 6-(3-hydroxy-3-methylbutyn-1-yl)coumarin-3-carboxylic acid (2) was obtained in satisfactory yield as a result of the interaction of the starting coumarin 1 with 3-hydroxy-3-methylbutyne in the presence of bis(triphenylphosphino)palladium dichloride and copper(I) iodide.…”
mentioning
confidence: 99%
“…The basic drawback of furocoumarins is their high phototoxicity. On the other hand, the synthesis and investigation of a series of organic and inorganic selenium compounds in many cases revealed a wide spectrum of biological activity, in particular selenium-containing derivatives showed the possibility of their use in the treatment of malignant tumors [4][5][6].…”
mentioning
confidence: 99%